2015
DOI: 10.1002/2015jb012074
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate rifted margins width and asymmetry: The interplay between lithospheric strength and thermomechanical processes

Abstract: Numerical experiments have been used to relate the range in the distribution and the style of deformation observed in rifted margins to localizing/delocalizing thermomechanical processes. The experiments give rise to four end‐members of margins for varying initial lithospheric strength and extension rates. The first two end‐members are narrow and asymmetric and narrow and near‐symmetric, conjugate margins. The third end‐member is asymmetric conjugate margins, wherein one side is <100 km wide and the other is >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
98
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 116 publications
13
98
0
Order By: Relevance
“…Full explanation of the models can be found in Svartman Dias et al . []. We present a type example in Figure .…”
Section: Lithosphere Stretching and Numerical Modelssupporting
confidence: 85%
See 3 more Smart Citations
“…Full explanation of the models can be found in Svartman Dias et al . []. We present a type example in Figure .…”
Section: Lithosphere Stretching and Numerical Modelssupporting
confidence: 85%
“…In Svartman Dias et al . [] we explored this effect by systematically changing initial crustal thickness, crustal strength, and the temperature field (thermal age) for numerous models employing the Fast Lagrangian Analysis of Continua method [ Cundall , ; Poliakov et al ., ]. The model results showed that the width and asymmetry of margins is highly dependent on initial conditions: (i) thicker/hotter original crust—with significant ductile lower crustal thickness—leads to wider asymmetric extensional systems and (ii) hotter and/or weaker mantle tends to enhance the asymmetry of these systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors that influence the style of rifting are the presence of preexisting weaknesses such as large faults or varying *Current address: BHP Billiton, 1500 Post Oak Boulevard, Houston, Texas 77056, USA amounts of decompression melting in the rising asthenosphere (Huismans and Beaumont, 2007;Armitage et al, 2009;Van Avendonk et al, 2009;Svartman Dias et al, 2015). We can improve our understanding of rift evolution if we compare the deep structure of mature rifted margins and consider the geological setting.…”
Section: Introductionmentioning
confidence: 99%